Preparation method of flexible hydrogen conveying pipe
By blending polychloroethylene, nylon 11, polyvinylidene fluoride and other materials, and spraying the reduced graphene oxide/polyethyleneimine composite materials on the inner wall of the flexible hydrogen transport tube, the shortcomings of existing hydrogen transport tubes in gas barrier properties and mechanical strength are solved, achieving more efficient hydrogen transmission and lower maintenance costs.
Patent Information
- Application Number
- CN202411725349.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing flexible hydrogen transport pipes have shortcomings in the barrier properties and mechanical strength of hydrogen, resulting in high hydrogen loss and maintenance costs.
Polychloroethylene trifluoroethylene, nylon 11, polyvinylidene fluoride, micro-nanocarbon materials, polyethyleneimine and other materials are blended, combined with spraying technology of reducing graphene oxide/polyethyleneimine composite materials, a gas barrier film is formed to improve gas barrier performance, and mechanical strength is enhanced by the addition of graphene microsheets.
It significantly improves the gas barrier performance and mechanical strength of the flexible hydrogen transport pipe, reduces hydrogen permeability, extends the service life of the pipe, and reduces maintenance costs.
Smart Images

Figure CN119505446A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of manufacturing flexible hydrogen transmission pipes, and specifically provides a method for preparing a flexible hydrogen transmission pipe. Background Art
[0002] Hydrogen, as a clean and efficient renewable energy, has attracted widespread attention and research enthusiasm in the energy field. This trend has strongly promoted the vigorous development of the hydrogen energy storage and transportation industry. Among the ways of transporting hydrogen energy, pipeline transportation has become one of the commonly used means due to its convenience. However, it is worth noting that due to the harsh conditions and complex operating environment involved in the hydrogen transportation process, the requirements for hydrogen pipeline materials are also extremely strict. These materials not only need to have excellent corrosion resistance to cope with possible chemical erosion, but also must have excellent gas barrier properties to ensure the safe and efficient transmission of hydrogen.
[0003] At present, mainstream hydrogen pipelines are mostly constructed of metal materials. Although they meet the basic needs of hydrogen transmission to a certain extent, they are susceptible to hydrogen corrosion and the subsequent maintenance costs are quite high. On the other hand, although flexible hydrogen pipelines have advantages in flexibility and ease of installation, they have obvious shortcomings in hydrogen barrier properties, resulting in a hydrogen loss problem that cannot be ignored. In view of this, the development of a polymer material with both excellent corrosion resistance and high-efficiency gas barrier properties has become the key to the hydrogen energy industry's move towards safe, economical and lightweight development. The research and development and application of this type of new material will hopefully provide strong support for the efficient and stable transmission of hydrogen.
[0004] The published patent CN104455765A discloses a hydrogen delivery pipe, which uses a polyamide-based material with strong elution resistance as the inner layer, and an outer layer made of polyurethane to prevent hydrogen penetration; although the polyurethane material has good stability, chemical resistance, resilience and mechanical properties, its weather resistance is poor when used outdoors, and problems such as powdering and loss of gloss may occur. For hydrogen delivery pipes exposed to the outdoors for a long time, this may affect their service life and performance. The scheme mentions that the outer layer of polyurethane material is used to prevent hydrogen penetration, but the barrier effect of polyurethane material on hydrogen is not very ideal.
[0005] At present, there is an urgent need for a hydrogen pipeline with excellent gas barrier properties and high strength. Summary of the invention
[0006] In view of the defects existing in the above prior art, the present invention provides a method for preparing a flexible hydrogen transmission pipe, and solves the problem of enhancing the gas barrier performance and mechanical strength of the flexible hydrogen transmission pipe.
[0007] The objective of the present invention is achieved through the following technical scheme. The raw material components of the flexible hydrogen transmission pipe include polytrifluorochloroethylene, nylon 11, polyvinylidene fluoride, micro-nano carbon material, polyethyleneimine, a compatibilizer, a cross-linking agent, an antioxidant, a dispersant, and a light stabilizer. The compatibilizer is a thermoplastic copolymer, the cross-linking agent is a thermoplastic polyurethane copolymer, the micro-nano carbon material includes graphene oxide and graphene microsheets, the dispersant is one of EBS, EB-G, and PE wax, the antioxidant is antioxidant 1076, and the light stabilizer is one of benzophenone and 2-hydroxybenzoate. The preparation method of the flexible hydrogen transmission pipe comprises the following steps: S1: Nylon 11 and polyvinylidene fluoride and other raw materials are mixed evenly in an internal mixer, and after cooling under pressure, a PA11 / PVDF composite material is prepared for use; S2: mixing graphene oxide and polyethyleneimine at 85° C. to form a suspension, filtering and drying to obtain a reduced graphene oxide / polyethyleneimine composite material for later use; S3: Mix polytrifluorochloroethylene, PA11 / PVDF composite material, graphene microsheets, compatibilizer, crosslinking agent, antioxidant, dispersant and light stabilizer evenly and send them into an internal mixer for melt blending, monitor the blending torque in real time, and obtain the target composite material A after the torque is stable; S4: Composite material A is cooled to 160°C and fed into a screw extruder using a vacuum suction machine. The extrusion temperature is set to 180-200°C. The speed ratio of the suction machine to the extruder is 1:1-2.5. After compression and extrusion, a tube material is obtained. S5: dispersing the reduced graphene oxide / polyethyleneimine composite material in water, ultrasonicating for 1 h to obtain a homogeneous solution, and using a spray gun to quantitatively and uniformly spray the composite material homogeneous solution on the inner wall surface of the pipe material at 60° C. to form a uniform gas barrier film; S6: The pipe material sprayed with the gas barrier film coating is vacuum dried at 50° C. to completely remove water, thereby obtaining a flexible hydrogen transport pipe.
[0008] The present invention blends PCTFE with a PA11 / PVDF composite material and graphene microsheets, so that the elongation at break and the impact strength of the flexible hydrogen transmission pipe are greatly improved compared with pure PCTFE pipes, and the toughness of the hydrogen transmission pipe is greatly increased; at the same time, the addition of PA11 improves the gas barrier performance of PCTFE, but the compatibility of PA11 and PCTFE is poor. The composite material made of PA11 and PVDF and then blended with PCTFE can reduce the occurrence of phase separation, and the addition of PA11 can also accelerate the crystallization of PCTFE. The rate improves the crystallization ability; the addition of graphene microsheets has a small effect on the increase of the elongation at break of the flexible hydrogen pipe, but the graphene microsheets are oriented under force during the processing so that most of them are arranged in parallel perpendicular to the cross section, which greatly extends the diffusion path of the gas molecules and establishes a structural advantage for the improvement of barrier performance, greatly improving the gas barrier performance of the hydrogen pipe; finally, the gas barrier film mainly formed by reduced graphene oxide / polyethyleneimine composite materials can form a protective layer with extremely strong gas barrier performance on the inner wall of the hydrogen pipe, and reduce the penetration of hydrogen through double-layer barrier.
[0009] In the above-mentioned method for preparing a flexible hydrogen transmission pipe, preferably, the compatibilizer is one of styrene-acrylonitrile copolymer, styrene-butadiene block copolymer, hydrogenated styrene-butadiene block copolymer, etc., in which the ratio of styrene to thermoplastic material is 1:3~4, and the preparation temperature is 120~130°C.
[0010] In the above-mentioned method for preparing a flexible hydrogen transmission pipe, preferably, the cross-linking agent is a hydroxyl-terminated poly(ester-urethane) copolymer, and the hydroxyl-terminated poly(ester-urethane) copolymer is prepared by mixing the prepolymer and the multifunctional isocyanate in a mass ratio of 10:1.
[0011] Further, poly(ester-urethane) copolymers are prepared by polymerizing a hydroxy-terminated ester-urethane prepolymer with a polyfunctional isocyanate (TDI); the prepolymer is a polyester polyol, a low molecular weight aliphatic or aromatic polymer having two OH terminal groups, and the isocyanate is characterized by a -NCO group that is highly reactive with alcohols.
[0012] In the above-mentioned method for preparing a flexible hydrogen transmission pipe, preferably, in the step S1, the mass ratio of the nylon 11 to the polyvinylidene fluoride is 1:4~8, the mixing temperature is 180~190°C, the rotation speed is 10~25r / min, the vulcanization temperature is 180~200°C, and the molding pressure is 10~15MPa.
[0013] In the above-mentioned method for preparing a flexible hydrogen transmission pipe, preferably, in the step S2, the mass ratio of the graphene oxide to the polyethyleneimine is 1:1~5. After the addition is completed, stirring is performed at 1400r / min for 20h, and a cellulose acetate membrane with a pore size of 0.2mm is used for filtration, and the drying temperature is 50~60°C.
[0014] In the above-mentioned method for preparing a flexible hydrogen transmission pipe, preferably, in the step S3, the blending temperature is 214-230°C.
[0015] In the above-mentioned method for preparing a flexible hydrogen transmission pipe, preferably, in the step S3, the addition amount of the PA11 / PVDF composite material is 5~10wt%, the addition amount of the dispersant is 0.7~1.3wt%, the addition amount of the antioxidant is 1.5~2wt%, the addition amount of the graphene microsheets is 0.1~0.5wt%, and the addition amount of the light stabilizer is 0.4~1wt%.
[0016] In the above-mentioned method for preparing a flexible hydrogen transmission pipe, preferably, in the step S5, the added amount of the reduced graphene oxide / polyethyleneimine composite material is 5-10wt%.
[0017] In the above-mentioned method for preparing a flexible hydrogen transmission pipe, preferably, in the step S5, the single spraying amount of the spray gun is 6 ml of homogeneous solution.
[0018] In the above-mentioned method for preparing a flexible hydrogen transmission pipe, preferably, after the completion of step S4, the prepared flexible hydrogen transmission pipe needs to be cooled, and a pressure of 14 to 26 MPa is applied to the flexible hydrogen transmission pipe during cooling.
[0019] Furthermore, as the cooling pressure increases, the crystallinity of PCTFE in the hydrogen transmission pipe gradually decreases, while the elongation at break increases significantly.
[0020] In summary, compared with the prior art, the present invention has the following advantages: 1. In the scheme of the present invention, PCTFE is blended with PA11 / PVDF composite material and graphene microsheets, so that the elongation at break and impact strength of the flexible hydrogen transmission pipe are greatly improved compared with pure PCTFE pipe, which greatly increases the toughness of the hydrogen transmission pipe; 2. In the scheme of the present invention, PA11 and PVDF are made into a composite material and then blended with PCTFE, which can improve the compatibility of PA11 and PCTFE and reduce the occurrence of phase separation. The PA11 / PVDF composite material has both the good weather resistance, chemical resistance and gas barrier properties of PVDF and the excellent processability and mechanical properties of PA11. Compared with pure PCTFE, the tensile strength of the PCTFE and PA11 / PVDF composite material after blending is not much improved, the elastic modulus is slightly decreased, but the elongation at break and the gas barrier properties are greatly improved; 3. In the scheme of the present invention, the blending of graphene microsheets and PCTFE can promote the nucleation of PCTFE, but the elongation at break of the flexible hydrogen pipe is slightly improved. Due to the special force direction of the graphene microsheets during the processing, most of them are arranged perpendicular to the cross section and in parallel, which greatly prolongs the diffusion path of the gas molecules, establishes a structural advantage for the improvement of the gas barrier performance, and greatly improves the gas barrier performance of the hydrogen pipe; 4. In the scheme of the present invention, copolymers such as styrene-acrylonitrile copolymers are used as compatibilizers, and hydroxyl-terminated poly(ester-urethane) copolymers [prepolymers are used as cross-linking agents. Since hydroxyl-terminated poly(ester-urethane) copolymers have excellent cross-linking effects on both the fluorine-containing polymer layer and the fluorine-free polymer layer, the compatibility and blending effect of PCTFE and PA11 / PVDF composites can be improved, and the occurrence of phase separation can be reduced; 5. In the scheme of the present invention, PEI uses its highly active amine groups to reduce graphene oxide, thereby forming a polymer composite material with excellent gas barrier effect. A homogeneous solution of reduced graphene oxide / polyethyleneimine composite material is coated on the inner wall of the hydrogen transmission pipe to form a gas barrier film, which can form a protective layer with extremely strong gas barrier performance on the inner wall of the hydrogen transmission pipe, and reduce the permeation of hydrogen through double-layer barrier. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0022] In order to explain the technical content, structural features, achieved objectives and effects of the present invention in detail, further description is given below in conjunction with specific embodiments.
[0023] a. Preparation of PA11 / PVDF composite materials: Prepare 20% PA11 and 80% PVDF powder according to the weight ratio, set the temperature to 190°C and mix them evenly at 20r / min in an internal mixer; transfer to a flat vulcanizer, set the temperature to 190°C and 15MPa, and mold for 30 minutes, then cool under pressure to obtain a PA11 / PVDF alloy material.
[0024] b. Preparation of rGO / HPEI composite materials: GO and HPEI were prepared in a weight ratio of 1:5, and the GO dispersion was slowly added to the HPEI solution and stirred to prepare a suspension. The suspension was stirred at 85°C and 1400 r / min for 20 h until the yellow-brown graphene oxide suspension turned black to form reduced graphene oxide. The suspension was vacuum filtered using a cellulose acetate membrane with a pore size of 0.2 mm, the filter cake was washed with water, and dried in a vacuum oven at 50°C to obtain a black product, namely, reduced graphene oxide / polyethyleneimine composite material (rGO / HPEI).
[0025] c. Preparation of styrene-acrylonitrile copolymer (compatibilizer): A certain amount of toluene is added into the container, and two equal amounts of styrene and acrylonitrile are prepared in a weight ratio of 1:4. One of the styrene and acrylonitrile is added first, the reaction system is heated to 120°C and the mixture is stirred for reaction at a stirring rate of 250rpm / min. Nitrogen is introduced for protection, and then the other styrene solution and acrylonitrile solution are slowly added dropwise to the reaction system for 6 hours. After the reaction liquid temperature is cooled to room temperature, ethyl acetate is added and stirred to precipitate the reaction product. After filtering, the filter cake is washed with ethyl acetate, and the process is repeated several times. The product is placed in a vacuum oven at 50°C and dried to obtain a styrene-acrylonitrile copolymer, i.e., a compatibilizer.
[0026] d. Preparation of PCTFE / PA11-5 / graphite composite materials by melt blending process: The following materials were prepared in proportion: 82.8wt% PCTFE, 5wt% PA11 / PVDF composite material, 0.3wt% GMS, 2wt% styrene-acrylonitrile copolymer, 2wt% poly(ester-urethane) copolymer, 1.5wt% antioxidant 1076, 1wt% EBS, 0.4wt% benzophenone, 5wt% rGO / HPEI composite material; PCTFE, PA11 / PVDF composite material, GMS, styrene-acrylonitrile copolymer, EBS, poly(ester-urethane) copolymer, antioxidant 1076 and benzophenone were mixed uniformly and sent into an internal mixer. The blending temperature was set to 217°C and the screw speed was set to 50 rpm / min for melt blending. The blending torque was monitored in real time. After the torque was stabilized, the target composite material A, namely PCTFE / PA11 / PVDF / GMS-0.3, was obtained (the obtained composite materials were named according to the proportion of graphite fillers, for example: PCTFE / PA11 / PVDF / GMS-0.3 means that the mixing proportion of GMS in the composite material is 0.3wt%).
[0027] e. Preparation of hydrogen pipe materials: The molten PCTFE / PA11 / PVDF / GMS-0.3 raw material was cooled to 160°C and sucked into the extrusion equipment by a vacuum suction machine. The extrusion temperature was set to 190°C, and the speed ratio of the suction machine and the extrusion equipment was 1:1. The hydrogen tube blank was obtained by compression and extrusion. The hydrogen tube blank was adhered to the traction screw, and the traction speed was set to 30m / min. The traction machine was started to slowly introduce the hydrogen tube blank into the cooling and shaping equipment. The cooling temperature was set to 15°C and a pressure of 26MPa was applied at the same time. After cooling, the shaping was completed to obtain the hydrogen tube material.
[0028] f. Spray gas barrier film on the inner wall of hydrogen transmission pipe: The rGO / HPEI composite material was dispersed in a certain amount of water and ultrasonicated for 1 hour to obtain a homogeneous solution. The composite suspension heated to 60°C was sprayed evenly onto the inner wall of the hydrogen delivery pipe material using a spray gun. The single spray volume of the spray gun was 6 ml of homogeneous solution. During the spraying process, the distance between the spray gun and the inner wall surface of the hydrogen delivery pipe material remained unchanged. Finally, the hydrogen delivery pipe material was vacuum dried at 50°C to completely remove water to form a uniform gas barrier film, which was the final product, the hydrogen delivery pipe.
[0029] Prepare 37% PA11 and 83% PVDF powders by weight, set the temperature to 190°C and mix them evenly at 20r / min in an internal mixer; transfer to a flat vulcanizer, set the temperature to 190°C and 15MPa, mold for 30 minutes, and then cool under pressure to obtain PA11 / PVDF alloy material a; Prepare 14.3% PA11 and 85.7% PVDF powders by weight, set the temperature to 190°C and mix them evenly at 20r / min in an internal mixer; transfer to a flat vulcanizer, set the temperature to 190°C and 15MPa, mold for 30 minutes, and then cool under pressure to obtain PA11 / PVDF alloy material b; Prepare 12.5% PA11 and 87.5% PVDF powders according to the weight ratio, set the temperature to 190°C and mix them evenly at 20r / min in an internal mixer; transfer to a flat vulcanizer, set the temperature to 190°C and 15MPa, mold for 30 minutes, and then cool under pressure to obtain PA11 / PVDF alloy material c; Prepare 11.1% PA11 and 88.9% PVDF powders according to the weight ratio, set the temperature to 190°C and mix them evenly at 20r / min in an internal mixer; transfer them to a flat vulcanizer, set the temperature to 190°C and 15MPa, and mold for 30 minutes, then cool under pressure to obtain PA11 / PVDF alloy material d.
[0030] The hydrogen transmission pipes were prepared using PA11 / PVDF alloy material, PA11 / PVDF alloy material a, PA11 / PVDF alloy material b, PA11 / PVDF alloy material c, and PA11 / PVDF alloy material d, and their performance tests were carried out respectively. The hydrogen transmission pipe prepared using PA11 / PVDF alloy material had the lowest hydrogen permeability, which was only 3.82×10 –15 cm 3 cm / (cm 2 ·h·Pa); Other test results are shown in the table below: .
[0031] GO and HPEI were prepared in a weight ratio of 1:4, GO dispersion was slowly added to HPEI solution, and a suspension was prepared by stirring, and the suspension was stirred at 85°C and 1400 r / min for 20 h until the yellow-brown graphene oxide suspension turned black to form reduced graphene oxide, and the suspension was vacuum filtered using a cellulose acetate membrane with a pore size of 0.2 mm, the filter cake was washed with water, and dried in a vacuum oven at 50°C to obtain a black product, namely reduced graphene oxide / polyethyleneimine composite material a (rGO / HPEI-a); GO and HPEI were prepared in a weight ratio of 1:3, GO dispersion was slowly added to HPEI solution, and a suspension was prepared by stirring, and the suspension was stirred at 85°C and 1400 r / min for 20 h until the yellow-brown graphene oxide suspension turned black to form reduced graphene oxide, and the suspension was vacuum filtered using a cellulose acetate membrane with a pore size of 0.2 mm, the filter cake was washed with water, and dried in a vacuum oven at 50°C to obtain a black product, namely, reduced graphene oxide / polyethyleneimine composite material b (rGO / HPEI-b); GO and HPEI were prepared in a weight ratio of 1:2, GO dispersion was slowly added to HPEI solution, and a suspension was prepared by stirring, and the suspension was stirred at 85°C and 1400 r / min for 20 h until the yellow-brown graphene oxide suspension turned black to form reduced graphene oxide, and the suspension was vacuum filtered using a cellulose acetate membrane with a pore size of 0.2 mm, the filter cake was washed with water, and dried in a vacuum oven at 50°C to obtain a black product, namely reduced graphene oxide / polyethyleneimine composite material c (rGO / HPEI-c); GO and HPEI were prepared in a weight ratio of 1:1, and the GO dispersion was slowly added to the HPEI solution and stirred to prepare a suspension. The suspension was stirred at 85°C and 1400 r / min for 20 h until the yellow-brown graphene oxide suspension turned black to form reduced graphene oxide. The suspension was vacuum filtered using a cellulose acetate membrane with a pore size of 0.2 mm, the filter cake was washed with water, and dried in a vacuum oven at 50°C to obtain a black product, namely, reduced graphene oxide / polyethyleneimine composite material d (rGO / HPEI-d).
[0032] rGO / HPEI, rGO / HPEI-a, rGO / HPEI-b, rGO / HPEI-c, and rGO / HPEI-d were used to prepare hydrogen delivery tubes, and the gas barrier performance tests were carried out respectively. The hydrogen delivery tube prepared by rGO / HPEI had the lowest hydrogen permeability, which was only 3.35×10 –15 cm 3 cm / (cm 2 ·h·Pa).
[0033] A. Prepare the following materials in proportion: 83wt% PCTFE, 5wt% PA11 / PVDF composite material, 0.1wt% GMS, 2wt% styrene-acrylonitrile copolymer, 2wt% poly(ester-urethane) copolymer, 1.5wt% antioxidant 1076, 1wt% EBS, 0.4wt% benzophenone, 5wt% rGO / HPEI composite material; PCTFE, PA11 / PVDF composite material, GMS, styrene-acrylonitrile copolymer, EBS, poly(ester-urethane) copolymer, antioxidant 1076, and benzophenone were mixed uniformly and sent into an internal mixer. The blending temperature was set to 217° C. and the screw speed was set to 50 rpm / min for melt blending. The blending torque was monitored in real time. When the torque was stable, the target composite material A, i.e., PCTFE / PA11 / PVDF / GMS-0.1, was obtained. B. Prepare the following materials in proportion: 82.9wt% PCTFE, 5wt% PA11 / PVDF composite material, 0.2wt% GMS, 2wt% styrene-acrylonitrile copolymer, 2wt% poly(ester-urethane) copolymer, 1.5wt% antioxidant 1076, 1wt% EBS, 0.4wt% benzophenone, 5wt% rGO / HPEI composite material; PCTFE, PA11 / PVDF composite material, GMS, styrene-acrylonitrile copolymer, EBS, poly(ester-urethane) copolymer, antioxidant 1076, and benzophenone were uniformly mixed and sent into an internal mixer, the blending temperature was set to 217° C., the screw speed was set to 50 rpm / min, melt blending was performed, and the blending torque was monitored in real time. After the torque was stable, the target composite material A, i.e., PCTFE / PA11 / PVDF / GMS-0.2, was obtained; C. Prepare the following materials in proportion: 82.7wt% PCTFE, 5wt% PA11 / PVDF composite material, 0.4wt% GMS, 2wt% styrene-acrylonitrile copolymer, 2wt% poly(ester-urethane) copolymer, 1.5wt% antioxidant 1076, 1wt% EBS, 0.4wt% benzophenone, 5wt% rGO / HPEI composite material; PCTFE, PA11 / PVDF composite material, GMS, styrene-acrylonitrile copolymer, EBS, poly(ester-urethane) copolymer, antioxidant 1076, and benzophenone were mixed uniformly and sent into an internal mixer. The blending temperature was set to 217° C. and the screw speed was set to 50 rpm / min for melt blending. The blending torque was monitored in real time. When the torque was stable, the target composite material A, i.e., PCTFE / PA11 / PVDF / GMS-0.4, was obtained. D. Prepare the following materials in proportion: 82.6wt% PCTFE, 5wt% PA11 / PVDF composite material, 0.5wt% GMS, 2wt% styrene-acrylonitrile copolymer, 2wt% poly(ester-urethane) copolymer, 1.5wt% antioxidant 1076, 1wt% EBS, 0.4wt% benzophenone, 5wt% rGO / HPEI composite material; PCTFE, PA11 / PVDF composite material, GMS, styrene-acrylonitrile copolymer, EBS, poly(ester-urethane) copolymer, antioxidant 1076, and benzophenone were mixed uniformly and sent into an internal mixer. The blending temperature was set to 217° C. and the screw speed was set to 50 rpm / min for melt blending. The blending torque was monitored in real time. When the torque was stable, the target composite material A, i.e., PCTFE / PA11 / PVDF / GMS-0.5, was obtained. PCTFE / PA11 / PVDF / GMS-0.3, PCTFE / PA11 / PVDF / GMS-0.1, PCTFE / PA11 / PVDF / GMS-0.2, PCTFE / PA11 / PVDF / GMS-0.4, and PCTFE / PA11 / PVDF / GMS-0.5 were used to prepare hydrogen delivery pipes, and their performance tests were carried out respectively. The hydrogen permeability of the hydrogen delivery pipe prepared by PCTFE / PA11 / PVDF / GMS-0.3 was 4.13×10 –15 cm 3 cm / (cm 2 ·h·Pa), the hydrogen permeability of the hydrogen transmission pipe prepared by PCTFE / PA11 / PVDF / GMS-0.5 is as low as 4.01×10 –15 cm3 cm / (cm 2 ·h·Pa), but the hydrogen permeability can no longer be significantly reduced with the continued increase in the amount of GMS added. At the same time, the elongation at break will gradually decrease significantly with the increase in the amount of GMS added.
[0034] The following materials were prepared in proportion: PCTFE (81.8wt%, 80.8wt%, 79.8wt%, 78.8wt%, 77.8wt%), PA11 / PVDF composite material (6wt%, 7wt%, 8wt%, 9wt%, 10wt%), 0.3wt% GMS, 2wt% styrene-acrylonitrile copolymer, 2wt% poly(ester-urethane) copolymer, 1.5wt% antioxidant 1076, 1wt% EBS, 0.4wt% benzophenone, 5wt% rGO / HPEI composite material, and 5 target composite materials A, namely PCTFE / PA11 / PVDF / GMS-0.3 (a, b, c, d, e) were prepared; Five kinds of composite materials were used to prepare hydrogen transport pipes, and their performance tests were carried out respectively. The hydrogen permeability of the hydrogen transport pipe prepared by the composite material in Example 1 was 3.82×10 –15 cm 3 cm / (cm 2 ·h·Pa), and can achieve a balance between elongation at break and hydrogen permeability. With the increase of PA11 / PVDF addition, the toughness of the hydrogen transmission pipe will decrease sharply. When the PA11 / PVDF addition is 5wt%, the elongation at break is 301.7%, while when the PA11 / PVDF addition is increased to 10wt%, the elongation at break is only 198.3%.
[0035] Prepare the following materials in proportion: PCTFE, 5wt% PA11 / PVDF composite material, 0.3wt% GMS, styrene-acrylonitrile copolymer (1.5wt%, 1.8wt%), 2wt% poly(ester-urethane) copolymer (1.2wt%, 2.2wt%), 1.5wt% antioxidant 1076, 1wt% EBS, 0.4wt% benzophenone, 5wt% rGO / HPEI composite material, and prepare 4 target composite materials A, namely PCTFE / PA11 / PVDF / GMS-0.3; Four kinds of composite materials were used to prepare hydrogen pipes, and their performance tests were carried out respectively. The elongation at break of the composite material prepared in Example 1 was 301.7%. With the increase of the amount of compatibilizer and cross-linking agent added, the hydrogen permeability of the hydrogen pipe was greatly reduced, while the toughness was improved to a maximum of 314%. The hydrogen permeability was 6.96×10 –15 cm 3 cm / (cm 2 ·h·Pa), not applicable to hydrogen transmission pipes.
[0036] Prepare the following materials in proportion: PCTFE, 5wt% PA11 / PVDF composite material, 0.3wt% GMS, 2wt% styrene-acrylonitrile copolymer, 2wt% poly(ester-urethane) copolymer, antioxidant 1076 (1.8wt%, 2wt%), EBS (0.7wt%, 1.3wt%), 0.4wt% benzophenone, 5wt% rGO / HPEI composite material, and prepare 4 target composite materials A, namely PCTFE / PA11 / PVDF / GMS-0.3; Four kinds of composite materials were used to prepare hydrogen transmission pipes, and their performance tests were carried out respectively. The elongation at break of the composite material prepared in Example 1 was 301.7%. When the proportion of the dispersant gradually increased, the tensile strength changed slightly, the elastic modulus decreased slightly, and the elongation at break showed a trend of first increasing and then decreasing. When the proportion of the dispersant gradually increased, the toughness changed less.
[0037] Prepare the following materials in proportion: 82wt% PCTFE, 5wt% PA11 / PVDF composite material, 0.3wt% GMS, 2wt% styrene-acrylonitrile copolymer, 2wt% poly(ester-urethane) copolymer, 1.5wt% antioxidant 1076, 1wt% EBS, 0.4wt% benzophenone, rGO / HPEI composite material (6wt%, 7wt%, 8wt%, 9wt%, 10wt%), and prepare 5 target product hydrogen transport pipes; Five kinds of composite materials were used to prepare hydrogen pipes, and their performance tests were carried out respectively. The hydrogen permeability of the composite material prepared in Example 1 was 3.82×10 –15 cm 3 cm / (cm 2 ·h·Pa), and as the addition amount of rGO / HPEI composite material increases to 10wt%, the hydrogen permeability can reach 2.73×10 –15 cm3 cm / (cm 2 ·h·Pa), but at this time the gas barrier film coating on the inner wall of the hydrogen transmission pipe is thicker and has poor adhesion, making the coating easy to fall off.
[0038] The implementation of the present invention is not limited to the above embodiments. Without departing from the spirit and scope of the present invention, ordinary technicians in this field can make various changes and improvements to the present invention in form and detail, and these are considered to fall within the protection scope of the present invention.
Claims
1. A method for preparing a flexible hydrogen transport pipe, characterized in that: The raw material components of the flexible hydrogen transmission pipe include polytrifluorochloroethylene, nylon 11, polyvinylidene fluoride, micro-nano carbon material, polyethylene imine, a compatibilizer, a cross-linking agent, an antioxidant, a dispersant, and a light stabilizer. The compatibilizer is a thermoplastic copolymer, the cross-linking agent is a thermoplastic polyurethane copolymer, the micro-nano carbon material includes graphene oxide and graphene microsheets, the dispersant is one of EBS, EB-G, and PE wax, the antioxidant is antioxidant 1076, and the light stabilizer is one of benzophenone and 2-hydroxybenzoate. The preparation method of the flexible hydrogen transmission pipe includes the following steps: S1: Nylon 11 and polyvinylidene fluoride and other raw materials are mixed evenly in an internal mixer, and after cooling under pressure, a PA11 / PVDF composite material is prepared for use; S2: mixing graphene oxide and polyethyleneimine at 85° C. to form a suspension, filtering and drying to obtain a reduced graphene oxide / polyethyleneimine composite material for later use; S3: Mix polytrifluorochloroethylene, PA11 / PVDF composite material, graphene microsheets, compatibilizer, crosslinking agent, antioxidant, dispersant and light stabilizer evenly and send them into an internal mixer for melt blending, monitor the blending torque in real time, and obtain the target composite material A after the torque is stable; S4: Composite material A is cooled to 160°C and fed into a screw extruder using a vacuum suction machine. The extrusion temperature is set to 180-200°C. The speed ratio of the suction machine to the extruder is 1:1-2.
5. After compression and extrusion, a tube material is obtained. S5: dispersing the reduced graphene oxide / polyethyleneimine composite material in water, ultrasonicating for 1 h to obtain a homogeneous solution, and using a spray gun to quantitatively and uniformly spray the composite material homogeneous solution on the inner wall surface of the pipe material at 60° C. to form a uniform gas barrier film; S6: The pipe material sprayed with the gas barrier film coating is vacuum dried at 50° C. to completely remove water, thereby obtaining a flexible hydrogen transport pipe.
2. The method for preparing a flexible hydrogen transport pipe according to claim 1, characterized in that: The compatibilizer is one of styrene-acrylonitrile copolymer, styrene-butadiene block copolymer, hydrogenated styrene-butadiene block copolymer, etc. In the compatibilizer, the ratio of styrene to thermoplastic material is 1:3-4, and the preparation temperature is 120-130°C.
3. The method for preparing a flexible hydrogen transport pipe according to claim 1, characterized in that: The crosslinking agent is a hydroxyl-terminated poly(ester-urethane) copolymer, and the hydroxyl-terminated poly(ester-urethane) copolymer is prepared by mixing a prepolymer and a multifunctional isocyanate in a mass ratio of 10:
1.
4. The method for preparing a flexible hydrogen transport pipe according to claim 1, characterized in that: In the step S1, the mass ratio of the nylon 11 to the polyvinylidene fluoride is 1:4-8, the mixing temperature is 180-190° C., the rotation speed is 10-25 r / min, the vulcanization temperature is 180-200° C., and the molding pressure is 10-15 MPa.
5. The method for preparing a flexible hydrogen transport pipe according to claim 1, characterized in that: In the step S2, the mass ratio of the graphene oxide to the polyethyleneimine is 1:1-5. After the addition is completed, the mixture is stirred at 1400 r / min for 20 hours. A cellulose acetate membrane with a pore size of 0.2 mm is used for filtration, and the drying temperature is 50-60°C.
6. The method for preparing a flexible hydrogen transport pipe according to claim 1, characterized in that: In the step S3, the blending temperature is 214-230°C.
7. The method for preparing a flexible hydrogen transport pipe according to claim 1, characterized in that: In the step S3, the amount of the PA11 / PVDF composite material added is 5~10wt%, the amount of the dispersant added is 0.7~1.3wt%, the amount of the antioxidant added is 1.5~2wt%, the amount of the graphene microsheet added is 0.1~0.5wt%, the amount of the light stabilizer added is 0.4~1wt%, the amount of the compatibilizer added is 1.5~2wt%, and the amount of the cross-linking agent added is 1.2~2.2wt%.
8. The method for preparing a flexible hydrogen transport pipe according to claim 1, characterized in that: In the step S5, the added amount of the reduced graphene oxide / polyethyleneimine composite material is 5-10wt%.
9. The method for preparing a flexible hydrogen transport pipe according to claim 1, characterized in that: In the step S5, the single spraying amount of the spray gun is 6 ml of the homogeneous solution.
10. The method for preparing a flexible hydrogen transport pipe according to claim 1, characterized in that: After the step S4 is completed, the prepared flexible hydrogen transmission pipe needs to be cooled, and a pressure of 14-26 MPa is applied to the flexible hydrogen transmission pipe during cooling.
Citation Information
Patent Citations
Hydrogen transfer tube
CN104455765A
Flexible polymer dielectric material for electrical condenser and preparation thereof
CN101508841A
Gas separation membrane, preparation method thereof, and membrane type gas separation device
CN104524990A
Multilayer structure for transporting or storing hydrogen
CN117396332A
Reduced Graphene Oxide Barrier Materials
US20170106342A1
Cited By
Polyvinylidene fluoride-based composite material as well as preparation method and application thereof
CN121064582A